2017
DOI: 10.15605/jafes.03.02.09
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with the Activity and Severity of Graves’ Ophthalmopathy among Patients at the University of the Philippines Manila-Philippine General Hospital

Abstract: Background. Asians with Graves' ophthalmopathy (GO) may have earlier compressive features due to narrower orbital apex and increased orbital volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…The level of antibodies to thyroid-stimulating hormone receptors is statistically significantly higher in moderately severe endocrine ophthalmopathy 21.6 IU/l in comparison with mild endocrine ophthalmopathy 12.9 IU/l (p=0.001), which corresponds to the results of most researchers [6,10,12,13,14].…”
Section: Results Of the Research And Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The level of antibodies to thyroid-stimulating hormone receptors is statistically significantly higher in moderately severe endocrine ophthalmopathy 21.6 IU/l in comparison with mild endocrine ophthalmopathy 12.9 IU/l (p=0.001), which corresponds to the results of most researchers [6,10,12,13,14].…”
Section: Results Of the Research And Discussionsupporting
confidence: 83%
“…The titer of antibodies to thyroid-stimulating hormone receptors positively correlated with the degree of activity of endocrine ophthalmopathy (r = 0.41). Our results do not contradict the studies of domestic and foreign scientists [6,10,11,12].…”
Section: Results Of the Research And Discussionsupporting
confidence: 70%
“…Lat et al . [ 36 ] revealed that on multivariate analysis, male gender and elevated TRAb were found to be associated with severe disease (odds ratio [OR] 3.71, P = 0.041) and (OR 1.02, P = 0.007), respectively. A study in an Asian population failed to identify any relationship between T3 or T4 levels and GO.…”
Section: Discussionmentioning
confidence: 99%
“…37 In our series, duration of thyroid disease before/after the eye involvement was similar among the 3 groups, and this was in agreement with the findings of previous studies. 39,41 Male gender has been found to be an important risk factor of moderate-to-severe TED/DON development in many western reports, 9,30 but the impact of gender in predicting risk of GO progression has varied in previous Asian studies. 6,41,42 Lat et al reported that being male carried a four times higher risk of GO severity in a region of the Philippines 41 ; conversely, in Korean populations, female sex was found to be a potential risk factor of severe TED.…”
Section: Discussionmentioning
confidence: 99%